"Carbo-aromaticity" and novel carbo-aromatic compounds. (21st September 2015) - Cocq, Kévin; Lepetit, Christine; Maraval, Valérie; Chauvin, Remi
<x xml:space="preserve">Abstract</x> Recent advances in experimental and theoretical studies of carbo-benzene derivatives, along with the proposition of a generalization of the definition of aromaticity to the two-membered π-rings of triple bonds, suggest relevance for the notion of "carbo-aromaticity".